Debt overhang and non-distressed debt restructuring - Frantz, Pascal; Instefjord, Norvald (Journal of Financial Intermediation, 2019)
In this paper, we analyse the restructuring of debt in the presence of debt overhang. The firm starts out with a debt liability and an investment opportunity. Then with unrestructured debt, the firm maintains the current borrowing payments until default or investment. If the creditors allow the parties to restructure the debt with exchange offers, then the borrowing payments change as well as the default and investment points. We find that there is a unique optimal restructuring path which maintains debt at positive levels but defers default indefinitely. This path is optimal regardless of whether the debt holders or the firm control the process through superior bargaining power. Moreover, a debt-for-equity exchange to remove all existing debt takes place just before investment that is followed by the issue of an optimal amount of new debt as part of the funding for the investment cost. The optimal investment trigger is higher along the optimal restructuring path than it is for an unlevered firm. We discuss the findings in the light of existing empirical evidence.